Using the iPod Touch for Patient Health Behavior Assessment and Health Promotion in Primary Care - Forjuoh, Samuel N; Ory, Marcia G; Wang, Suojin; des Bordes, Jude KA; Hong, Yan (JMIR Publications, 2014)
BackgroundThere is a growing recognition of the importance of lifestyle behavior change for health promotion and disease prevention, as well as the concomitant influence of patient-physician communication on effective behavior change. Mobile technology is increasingly being recognized as an important and efficient tool to collect patients' health behavior data and facilitate patient-physician communication. ObjectiveThe aim of this study was to assess the feasibility of an iPod touch-based health behavior assessment (HBA) tool in enhancing patient-physician collaborative goal-setting for health promotion in primary care. MethodsA total of 109 patients from three primary care clinics in central Texas completed a brief HBA, which was programmed on an iPod touch device. An instant feedback report was generated for the patient and their physician simultaneously to facilitate collaborative goal-setting. Within approximately 7 days of the HBA, the patients were phoned for a follow-up survey for their feedback on the iPod touch-based HBA and resultant patient-physician communication. ResultsPatients were able to complete an HBA on the iPod touch with ease. Among those who completed the follow-up survey (n=83), 30% (25/83) reported that their physicians discussed the HBA report with them, while 29% (24/83) established behavior change goals with them. More than 90% (75/83) of the patients reported positive experiences with the iPod touch-based HBA. ConclusionsIt is feasible to use mobile tools for HBA in the primary care setting. The HBA also facilitated patient-physician communication on behavior change. However, more research is needed on the effectiveness of large scale dissemination of mobile-based HBA technology on health communication and behavior change for preventing or managing lifestyle-related chronic conditions, such as obesity, diabetes, cancer, or heart diseases.